PENILAIAN DAYA TARIK DAN PENGEMBANGAN KAWASAN TAMAN WISATA MANGROVE DI DUSUN TANAH MERAH KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Prahesty, Desintha Yuwindha; Muin, Sudirman; Fahrizal, . (JURNAL HUTAN LESTARI, 2018)
Ecotourism as a type of tourism based on the nature, was a green industry which must be planned sustainability. Kayong Utara regency has potential in natural resource one of them is Taman Wisata Mangrove (Mangrove Reserve Park). Otherwise, unfortunately it was unwell planned. Natural tourist attraction located in area Taman Wisata Mangrove which supported with existence of infrastructure, accommodation, accessibility, and so should be improved development especially if viewed from aspects of tourism. The method used is survey method with descriptive and used interview techniques with instrument a questionnaire. Analysis of data using analysis of Regional Operations Guidelines and Nature Attractions Directorate General PHKA 2003 and SWOT Analysis. The result showed rating attraction tourism object Taman Wisata Mangrove have value 553,05. After compared with the classification of business development of nature tourism, an area Taman Wisata Mangrove have valuation medium (B). This means potential developed into a tourist attraction.  Based on assessment for tourism development  strategy  Taman Wisata Mangrove are  in  quadrant  III  (WO  Strategy)  is  to maximize opportunities and minimize the threats that exist. As for the points for WO strategy namely: a. To developing mangrove ecotourism product in special interest tourism; b. Facilities in Taman Wisata Mangrove need to be added for the support mangrove tourism activities; c. Enhance human resource capability which have the competence standard in mangrove ecotourism development; d. Create the open public information especially about special interest activities in mangrove ecotourism on website; e. Enhance coordination with  local government about the cleanliness and preserveness of ecotourism site in Taman Wisata Mangrove.Keywords: Development, Ecotourism, Mangrove, Taman Wisata Mangrove, Tourist Attraction